Body symmetry and physical strength in human males. Issue 5 (5th July 2014) - Fink, Bernhard; Weege, Bettina; Manning, John T.; Trivers, Robert
Abstract : Objectives: Body symmetry and physical strength in males have been related to aspects of mate "quality"—women seem to prefer men who display both "good genes" (as indexed by high symmetry/developmental health) and fighting ability (as indexed by physical strength). Here we show that fluctuating asymmetry (FA) of the body and physical strength are negatively correlated. Methods: Body FA (from 12 paired traits) and handgrip strength (HGS; a measure of muscular power and force) were measured in a sample of 69 heterosexual, right‐handed men (18–42 years). Results: There were positive correlations of body symmetry with HGS after controlling for the effect of body‐mass‐index. Conclusions: We conclude that in males, body symmetry and physical strength are correlated such that symmetric individuals tend to develop higher strength, which may contribute to their success in inter‐ and intra‐sexual selection. Am. J. Hum. Biol. 26:697–700, 2014. © 2014 Wiley Periodicals, Inc.